Migrant Work by Another Name: Differential Inclusion and Precarity in Canada’s International Mobility Program - Vosko, Leah F. (Studies in comparative political economy and public policy, 2025)
Migrant Work by Another Name explores the complexities of Canada's evolving international migration and employment policy landscape. It critically examines the shift towards “mobility” programs under the recently inaugurated International Mobility Program (IMP). This shift occurs alongside the contraction of certain streams within Canada’s long-standing Temporary Foreign Worker Program (TFWP). The book investigates the implications of policy changes, influenced at once by public outcry over migrant worker exploitation and persistent demands for labour in the face of qualitative labour shortages in high-income countries like Canada. Grounded in a decolonial feminist political economy approach, Leah F. Vosko employs a mixed methods analysis to contrast the narrative of “mobility” with the persistent realities of precarity among transnational workers. The book features in-depth case studies of the three largest IMP subprograms – Working Holiday, Post-Graduation, and Spousal Work Permit programs – revealing how these initiatives, despite being touted as promoting mobility, provide for temporary migrant work by another name and perpetuate distinct forms of precarity. This critical perspective challenges the notion of progress in contemporary migration policies, shedding light on the ongoing challenges faced by transnational workers in Canada. -- Publisher's description
Keywords: Foreign workers Employment Government policy Canada Evaluation; International Mobility Program (Canada) Evaluation; Labor mobility Government policy Canada Evaluation; Main-d'œuvre Mobilité Politique gouvernementale Canada Évaluation

Employment Standards Database - York University. Global Labour Research Centre; York University. Department of Politics; Vosko, Leah F. (2025)
The Employment Standards Database is a research database for comparing employment standards, awareness and violations across national/regional context. It brings together a library of relevant sources, unique user-friendly statistical tables, and a thesaurus of concepts – designed to facilitate research on labour market insecurity in a comparative industrialized context. Users can analyze multidimensional tables to explore and compare the contours of precarious employment in Australia, Canada, the United States, and the United Kingdom. --Website description

Understanding Temporary Labour Migration through a Settler Colonial Lens: A Critical Analysis of Canada’s Seasonal Agricultural Worker Program and International Education Strategy - Spring, Cynthia; Toomey, Nisha; Noack, Andrea; Vosko, Leah F. (Studies in Social Justice, 2025)
The relationship between differential inclusion of workers migrating for employment internationally and the dispossession and assimilation of Indigenous people and lands is a growing area of study within critical migration studies. Less attention has been paid, however, to how (im)migration policies that foster migrant worker precariousness also extend settler colonial practices. Scholars situated in the transdisciplinary fields of Black Studies and Indigenous Studies have long theorized nation-state building as exclusionary to Black and Indigenous life, and reliant on limited mobilities and dispossession of Black and Indigenous peoples. Bridging this scholarship with critical migration studies, in this article we explore how policies regulating international migration for employment to Canada on temporary bases reflect and sustain the settler-colonial context in which they operate. We outline three logics of settler colonialism that underpin policies governing temporary migration for employment to Canada: (1) the racialized hierarchization of life and knowledge; (2) the reliance on technologies of governing, which foster unequal administrative burdens; and (3) the disruption of people’s relationships to land and livelihoods. Analyzing Canada’s Seasonal Agricultural Worker Program and International Education Strategy, we illustrate how migration policies reinforce and replicate settler colonial practices.
Keywords: Black Studies; Indigenous Studies; international students; settler colonialism; temporary labour migration

The ‘Contract’ and Its Discontents: Can It Address Protection Gaps for Migrant Agricultural Workers in Canada? - Basok, Tanya; Tucker, Eric M.; Vosko, Leah F.; Caxaj, C. Susana; Hennebry, Jenna L.; Mayell, Stephanie; McLaughlin, Janet; Weiler, Anelyse M. (International Migration, 2025)
Canada's Seasonal Agricultural Worker Program has often been portrayed as a model for temporary migration programmes. It is largely governed by the Contracts negotiated between Canada and Mexico and Commonwealth Caribbean countries respectively. This article provides a critical analysis of the Contract by examining its structural context and considers the possibilities and limitations for ameliorating it. It outlines formal recommendations that the article co-authors presented during the annual Contract negotiations between Canada and sending states in 2020. The article then explains why these recommendations were not accepted, situating the negotiation process within the structural context that produces migrant workers' vulnerability, on the one hand, and limits the capacity of representatives of sending and receiving states to expand rights and offer stronger protections to migrant farmworkers, on the other hand. We argue that fundamental changes are required to address the vulnerability of migrant agricultural workers. In the absence of structural changes, it is nevertheless important to seek improvements in the regulation of the programme through any means possible, including strengthening the Contract.